2018
DOI: 10.1016/j.bpsc.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic Effects of Ventromedial Prefrontal Cortex Transcranial Magnetic Stimulation on Cue Reactivity

Abstract: This is the first sham-controlled investigation to demonstrate, in two populations, that VMPFC cTBS can attenuate neural reactivity to drug and alcohol cues in frontostriatal circuits. These results provide an empirical foundation for future clinical trials that may evaluate the efficacy, durability, and clinical implications of VMPFC cTBS to treat addictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 65 publications
(79 reference statements)
5
62
0
Order By: Relevance
“…In a sham‐controlled neuroimaging study we demonstrated that continuous theta burst stimulation (cTBS) to the left frontal pole decreased functional connectivity between the MPFC and dorsal striatum when alcohol users were viewing alcohol vs. nonalcoholic beverage cues . Here we tested (and confirmed) the hypothesis that TBS‐associated change in frontal‐striatal connectivity is affected by multiple structural features of the brain, including the distance from the scalp location of the TMS coil to the cortex, the gray matter volume in the vicinity of the coil, and the white matter fiber tract integrity from the coil location to the striatum.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…In a sham‐controlled neuroimaging study we demonstrated that continuous theta burst stimulation (cTBS) to the left frontal pole decreased functional connectivity between the MPFC and dorsal striatum when alcohol users were viewing alcohol vs. nonalcoholic beverage cues . Here we tested (and confirmed) the hypothesis that TBS‐associated change in frontal‐striatal connectivity is affected by multiple structural features of the brain, including the distance from the scalp location of the TMS coil to the cortex, the gray matter volume in the vicinity of the coil, and the white matter fiber tract integrity from the coil location to the striatum.…”
mentioning
confidence: 63%
“…Generalized Psychophysiological Interaction was performed to evaluate task‐based functional connectivity with the MPFC during the alcohol cue‐reactivity tasks (see Kearney‐Ramos et al . for more detail). Diffusion‐weighted images were first evaluated for artifacts and excessive head motion.…”
Section: Design and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of consistency is common in rTMS research as there has not yet been a systematic approach to elucidate which parameters best achieve specific goals. Nonetheless, there is a general consensus on the target of stimulation: with the aim of modulating the mesocorticolimbic system, the majority of studies target the DLPFC, with only a few exceptions that stimulate the mPFC (Hanlon et al, 2015(Hanlon et al, , 2017Kearney-Ramos et al, 2018, 2019). In addition, most studies tend to stimulate only one side of the brain, usually the left, although a sham-controlled study comparing right-and left-side stimulations did not show a significant effect of laterality (Liu et al, 2017).…”
Section: Rtms In Cocaine and Methamphetamine Abuse -Clinical Researchmentioning
confidence: 99%
“…There are studies targeting other areas than the DLPFC within the frontal cortex, such as inferior frontal gyrus, ventromedial prefrontal, or middle frontal cortices. As an example, Kearney-Ramos et al demonstrated that applying continuous theta burst stimulation (cTBS) as a type of TMS to the ventromedial prefrontal cortex could attenuate the cuerelated functional connectivity (215). In another study, Ceccanti et al found out that deep TMS (dTMS) on the medial prefrontal cortex (MPFC) decreased craving and alcohol intake in people with alcohol use disorder.…”
Section: Brain Stimulation Studies In Sudmentioning
confidence: 99%